Bone loss in unclassified polyarthritis and early rheumatoid arthritis is better detected by digital x ray radiogrammetry than dual x ray absorptiometry: relationship with disease activity and radiographic outcome. Issue 1 (12th December 2003) - Jensen, T; Klarlund, M; Hansen, M; Jensen, K E; Pødenphant, J; Hansen, T M; Skjødt, H; Hyldstrup, L
Abstract : Objective: To compare changes in regional bone mineral density (BMD) of the metacarpal joints measured by dual x ray absorptiometry (DXA) and digital x ray radiogrammetry (DXR) in relation to disease activity and radiographic outcome in a two year follow up study of patients with early RA and unclassified polyarthritis. Patients and methods: 72 patients with symmetrically swollen and tender second and third metacarpophalangeal or proximal interphalangeal joints for at least four weeks and less than two years were included. 51 patients fulfilled the ACR criteria for RA. 21 patients had unclassified polyarthritis. The patients with RA were divided into groups according to mean disease activity, average glucocorticoid dose, and MRI and x ray detected bone erosions in the hands. Clinical and biochemical measurements were made every month and an x ray examination of the hands and BMD of the metacarpal joints every six months. Results: DXR BMD decreased significantly only in patients with RA from month 6 and was associated with the mean disease activity. Patients with RA and erosive as well as non-erosive disease showed a significant decrease in the rate of bone loss, greatest in those with erosive disease. No changes in BMD measured by DXA were seen in any patient group. Conclusion: DXR is a useful measure of the destructive disease activity in patients with RA and unclassified polyarthritis, providing valuable information about bone changes associated with disease activity and erosive disease in early RA. DXR is better than DXA for detecting and monitoring periarticular osteoporosis of the metacarpal bone.